Dosimetric Comparison and Plan Evaluation of Different Dose Computing Algorithms for Different Radiotherapy Techniques in Head and Neck Tumors - Bharath Pandu; KHANNA D; Mohandass P; Rajadurai Elavarasan; Vivek T R; Saro Jacob; Goutham Sunny; Hima Nainan; Tatarao Maddipati (Iranian Journal of Medical Physics, 2022)
Introduction: The study aims to compare target coverage and critical structure dose difference between various dose computing algorithms with small segment dose calculation in Intensity Modulated Radiation Therapy (IMRT) and large segment dose calculation in 3-Dimensional Conformal Radiation Therapy (3DCRT) treatment plan for Head and Neck (H&N) tumor.Material and Methods: For the present study, thirty-eight H&N cancer patients were selected retrospectively. Twenty-seven patients were planned with IMRT plan using Monte Carlo (MC) algorithm and eleven patients with 3DCRT plan using Collapsed Cone/Superposition (CCS) algorithm. IMRT plan was recalculated with Pencil Beam (PB) and the 3DCRT plan was recalculated with MC and PB algorithms. An Independent student t-test was performed as a part of statistical analysis for dosimetric comparison of the p-value.Results: In the IMRT plan, mean dose, Conformity Index (CI), D2%, D98%, and D50% showed a significant difference in p-values (p<0.05), but the critical structure did not have a significant difference in p-value between the MC and PB algorithms, except Planning Risk Volume (PRV) spine. In the 3DCRT plan, mean dose, CI, Homogeneity Index (HI), D98%, D50%,and all the critical structures showed no statistically significant p-values (p<0.05) between the CCS with MC and CCS with PB algorithms.Conclusion: The study concludes that in the IMRT treatment technique, PB algorithms overestimate the dose compared to the MC algorithm, even in the head and neck treatment area. For 3DCRT treatment plans, CCS, MC, and PB algorithms showed no statistically significant differences between them. Moreover, this study ensured the accuracy of various dose calculation algorithms in H&N radiotherapy.